To solve the system of equations:
We can use the method of substitution or elimination.
Using the method of substitution:
1) Solve one equation for one variable in terms of the other variable:
Rearrange the first equation to solve for x:
-x + 6y = 13
x = 6y - 13
2) Substitute the expression for x in the second equation:
4x - 10y = -10
4(6y - 13) - 10y = -10
24y - 52 - 10y = -10
14y - 52 = -10
14y = -10 + 52
14y = 42
y = 42/14
y = 3
3) Substitute the value of y into the expression for x:
x = 6y - 13
x = 6(3) - 13
x = 18 - 13
x = 5
Therefore, the solution to the system of equations is x = 5 and y = 3.
Solve the system of equations. –x+6y=13 4x–10y=–10 (1 point)
1 answer